CULTURE OF SILENCE: SCRUTINISING THE UN’S “ZERO TOLERENCE” APPROACH TO SEXUAL EXPLOITATION AND ABUSE IN PEACE KEEPING OPERATIONS - Ali Rıza Savaş; Adem Palabıyık; Orhan Orhun (İmgelem)
The peacekeeping operations of the United Nations for bringing peace and stability, which have been accepted by the country and have great expectations from the people, sometimes fail to give the desired contribution but confront the people of the country, especially women and young girls. The habit of sexual abuse and exploitation, which is gained in almost every operation in which the United Nations intervenes and carries out a peacekeeping operation with another problem such as sexual abuse and exploitation, is now turning into a trust problem towards the United Nations. The complex post-war environment in which the United Nations intervened through peacekeepers is further complicated by this widespread and exposed problem posed by these forces. In this sense, it becomes as important as necessary to investigate the reasons why sexual abuse and exploitation are so widespread and permanent. The solutions that the United Nations tries to bring to this problem are not effective enough, and an effective method cannot be developed for the solution of this problem that has become permanent. Sexual abuse and exploitation, which is already a big problem in the legal context, is a complex problem that needs to be also solved in the illegal context. In this study, the reasons for the emergence of this problem, which has become unacceptable especially for women and young girls, have been discussed, and the efforts of the United Nations for a solution and the adequacy of this effort have been examined through examples.